Outcome of neuropsychiatric symptoms related to an antiretroviral drug following its substitution by nevirapine: the RELAX study. Issue 10 (4th August 2015) - Pedrol, E; Llibre, JM; Tasias, M; Currán, A; Guardiola, JM; Deig, E; Guelar, A; Martínez‐Madrid, O; Tikhomirova, L; Ramírez, R; RELAX Study Group; Pedrol, E.; et al.
<x xml:space="preserve">Abstract</x> Objectives The primary objective was to evaluate the improvement in neuropsychiatric symptoms attributed to an antiretroviral drug after that drug was substituted with nevirapine. The secondary objective was to evaluate the impact on patient adherence and quality of life. Methods A prospective, observational study was carried out that included patients with HIV‐1 plasma suppression for whom an antiretroviral drug was substituted with nevirapine because of central nervous system (CNS) side effects, a Pittsburgh Sleep Quality Index (PSQI) score > 5 or a Hospital Anxiety and Depression Scale (HADS) score ≥ 10, and who had not initiated psychoactive drug treatment during the prior 6 weeks. Evaluations were carried out at baseline and 1 and 3 months after the switch using the PSQI, HADS, Epworth Sleepiness Scale, Medical Outcomes Study‐Short Form 30 items (MOS‐SF‐30) and Simplified Medication Adherence Questionnaire (SMAQ). Results A total of 129 patients were included in the study. The drug substituted was mainly efavirenz (89.9%), and reasons for the switch included sleep disturbances (75.2%), anxiety (65.1%), depression (38.7%), attention disturbances (31%), and other reasons (31%), with a mean of 2.4 neuropsychiatric disturbances per patient. A statistically significant improvement was observed in all the tests evaluating neuropsychiatric symptoms and adherence at 1 and 3 months. The CD4 lymphocyte count remained stable (P = 0.096). Three (2.3%) patients had a detectable plasma HIV‐1 RNA at the end of the study. Nine patients (6.9%) withdrew because of nevirapine‐related toxicity (rash in seven patients and hypertransaminasaemia in two patients, none of which were > grade 2). Conclusions The switch to nevirapine from a drug causing neuropsychiatric disturbances (primarily efavirenz) in subjects with virological suppression was effective in resolving those disturbances, with an improvement in all the parameters studied. This led to better adherence to treatment and quality of life, with no detrimental effect on their immunological and virological control.